Description of a new fossil Anthoxyela species (Hymenoptera, Xyelidae) from Yixian Formation of Northeast China - Gao, Taiping; Ren, Dong (Zootaxa, 2008)
This paper reports a new species Anthoxyela orientalis sp. nov. referred to the genus Anthoxyela Rasnitsyn, 1977 of the subfamily Macroxyelinae (Symphyta, Xyelidae). This fossil was collected from the Yixian Formation of western Liaoning, China. Based on characters of this specimen, the diagnosis of the genus Anthoxyela is revised.